In-vitro regeneration of orthosiphon stamineus (misai kucing) using axillary bud - Zainuddin, Zarina; Mohd Kamil, Asmaa' (Zibeline International Publishing, 2019)
Orthosiphon stamineus or known as Misai kucing is a popular herbal tea plant that helps in treating the ailments of kidney and bladder, diabetes mellitus and gout. Due to high demand of this medicinal plant, a large propagation of this plant is recommended. In this study, a protocol for regeneration of Orthosiphon stamineus using axillary bud as explant was established. Murashige and Skoog (MS) medium supplemented with various concentrations of 6-benzylaminopurine (BAP) were evaluated for their effects on shoot induction. Results obtained revealed that the best shooting ability was observed when explants were cultured on MS medium supplemented with 0.2 ppm of BAP. Subsequently, shoot elongation of established shoot was obtained in medium containing gibberelic acid (GA3) with concentration of 0.5 ppm and 1.0 ppm. The best shoot elongation was achieved with medium supplemented with 0.5 ppm of GA3. Subsequently, the elongated explants were transformed to root induction medium with the addition of either 0.2 ppm of 1-naphthaleneacetic acid (NAA) or 0.5 ppm NAA. The explants showed positive response in medium supplemented with 0.2 ppm of NAA. From this study it could be confirmed that suitable concentration of plant growth regulators could be used in the regeneration of Orthosiphon stamineus through tissue culture technique.